2017
DOI: 10.12681/bgsg.14281
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Urban Park Soils From Athens, Greece

Abstract: Urban geochemistry is a scientific discipline which is growing in the recent years mainly because of the environmental impact caused by urbanization. The present study aims to determine the concentrations of potentially harmful elements (PHEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…As far as the studied soils, the content of bioavailable forms of lead in the soils of Kielce was higher than in Olsztyn, comparing to the content of total forms. The analysis of the percentage share of bioavailable forms in the total content of lead did not clearly confirm the conclusions made by Papazotos et al [52].…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…As far as the studied soils, the content of bioavailable forms of lead in the soils of Kielce was higher than in Olsztyn, comparing to the content of total forms. The analysis of the percentage share of bioavailable forms in the total content of lead did not clearly confirm the conclusions made by Papazotos et al [52].…”
Section: Resultscontrasting
confidence: 79%
“…Papazotos et al [52] showed in their study on the soils of Athens that the higher the total content of this metal in the soils, the lower the level of extraction of exchangeable forms. As far as the studied soils, the content of bioavailable forms of lead in the soils of Kielce was higher than in Olsztyn, comparing to the content of total forms.…”
Section: Resultsmentioning
confidence: 99%
“…Pb is a toxic metal to humans, causing carcinogenic impacts and teratogenic abnormalities in humans, even at very low concentrations (32,28) . The high concentration of Pb recorded in QAE (1449, 27 μg L-1) may be due to the nature of anthropogenic activities connected with oil products and traffic (33,34) , the release of unsuccessfully treated waste effluents and Pb-containing pesticides. These results were therefore consistent in the rainwater samples analyzed (27,35) .…”
Section: The Chemical Deposition In Rainwatermentioning
confidence: 99%
“…Soil is known as an essential natural resource. Its layers are polluted mainly with inorganic contaminants released from industries such as food processing and other related activities (Papazotas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%